Experimental Study on Axial Compression Behavior of Fiber-Reinforced Lightweight Aggregate Concrete Columns Confined by Grid Stirrups - Shun Chen; Tao Wu; Yujie Huang; Guangyu Sun (Buildings)
In this study, thirteen axial compression tests were conducted on stirrup-confined fiber-reinforced lightweight aggregate concrete (SFLWAC) columns. The effects of stirrup spacing, fiber type, and fiber volume content on the confinement effect of concrete were analyzed. The failure process and failure modes were investigated. The stress–strain curve of columns and the characteristic points of the curve were examined, and prediction models for peak stress and strain were proposed. The results indicate that increasing the volumetric stirrup ratio effectively enhances the lateral confinement force and increases the area of confined concrete. For specimens with a low volumetric stirrup ratio, the stirrups do not fully utilize their strength when the confined concrete reaches peak strength. The addition of fibers effectively improves the brittleness of lightweight aggregate concrete, with steel fibers providing a more pronounced improvement than carbon fibers. The proposed prediction models can accurately predict the axial compression behavior of SFLWAC.